Pengaruh Teknik Relaksasi Genggam Jari Terhadap Tingkat Stres Perawat Di Ruang Critical Care Rs Dr Oen Kandang Sapi Solo - Melina, Agil; Handayani, Prita Adisty; Patriyani, Ros Endah Happy (LPPM UNIKAL, 2025)
Stress is a reaction or process that results in physical and psychological tension exceeding an individual's capabilities. It can manifest as an inability to cope with threats physically, mentally, emotionally, or spiritually, ultimately impacting physical health. The finger grip relaxation technique, or finger hold, involves reflecting points on the hand to provide reflex stimulation through gripping. A preliminary study in the critical care unit showed that 60% of nurses experienced moderate stress and 40% experienced mild stress. This study aims to determine the effect of finger-hold relaxation intervention on stress levels in nurses in the critical care unit at Dr. Oen Kandang Sapi Hospital, Solo. The design used in this research was a quasi-experimental approach with pre and post-tests. Data analysis was performed using the Wilcoxon test. The sampling technique was purposive sampling, with a sample size of 32 respondents. The study involved administering the Nurses' Work Stress Questionnaire (ENSS) before and after the finger-hold relaxation intervention, which was conducted over 2 weeks with 8 sessions. The research was carried out from May 13 to June 4, 2024. The test results showed a p-value of 0.000, indicating that Ho was rejected and Ha was accepted, meaning that the finger grip relaxation intervention significantly affected nurses' stress levels. It is recommended that this technique be applied continuously to maintain the mental health of nurses.